KAJIAN SISTEM MANAJEMEN K3 DAN TINGKAT KECELAKAAN KERJA PADA PEKERJAAN STRUKTUR BAJA DI PLTU TANJUNG JATI B UNIT 5 & 6 JEPARA - Khotibul Umam; Nur Hidayati; Yayan Adi Saputro; Dwika Fatimatuz Zaroh; Decky Rochmanto (Jurnal Disprotek, 2020)
Safety work management system at the company is very influential in preventing work accidents. Low awarness of workers level of law enforcement provided by the government, it can cause the application of regulations is not optimal, so that it can cause a high level of work accident. For this reason, it is necessary to conduct further studies on the safety work manajemen system. and do the analysis to determine the effectiveness of safety work management and occupational accident in a company. this research was conducted on PLTU Tanjung Jati B unit 5&6 development project. This reseacrh uses questionnaires to collect the data. the data is processed using the SPSS application with linear regression analysis. The results from this reseach is safety work manajemen system have a influance on the level of occupational accidents if applied simultaneously. The results of the simulation test are F count = 3,24 â‰¥ 3,09 F table, and occupational accidents that occur have no relationship with the safety work management system and the safety work program. The result in anova table have a velue Sig = 0,291 = 29,1 % > 5 % is nonlinear and multiple correlation analysis T = 0,25, there is no strong relation. Accidents that often occur can be categorized in human factor theory.